(untitled) (American Journal of Islam and Society, 2002)
Dialogue among the adherents of the major world religions has always taken place, especially, but not only, among the Abrahamic faiths: Judaism, Christianity and Islam. Excellent examples of this may be found in the midst of shared histories where we are more often presented with a record of conflicts. The high points must be the enormously rich and creative interactions which took place in medieval Islamic Spain and southern Italy and at various times in places as far apart as Central Asia, Baghdad, Delhi, Cairo and the Ottoman Empire. As a movement with its institutions and full-time professionals, and networks of activists, interreligious dialogue is primarily a phenomenon of the twentieth century. It is the pressures of this century which have demanded that we mobilize the resources of the great religions for dialogue and peace, purposes which have historically often seemed marginal. In India, the realization that a reasonably unified independence would only be achieved if religions could work together, actually provides a significant impetus towards the cooperation of religious leaders and institutions. The horrors of Nazi genocide in Europe spurred post-war generations towards a radical review of traditional Christian attitudes towards Judaism. Out of regional tragedies, like the wars in Lebanon and in the former Yugoslavia, have come strengthened efforts across the social spectrum to disarm religious hatreds. The resurgence, in the last couple of decades, of political radicalism motivated by religion and expressed in religious terms, ...